2019
DOI: 10.3390/foods8020079
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Challenge: Lactic Acid Bacteria Isolated from Bovine Udders versus Staphylococci

Abstract: Mastitis poses a considerable threat to productivity and to animal welfare on modern dairy farms. However, the common way of antibiotic treatment does not always lead to a cure. Unsuccessful cures can, among other reasons, occur due to biofilm formation of the causative agent. This has attracted interest from researchers to introduce promising alternative therapeutic approaches, such as the use of beneficial lactic acid bacteria (LAB). In fact, using LAB for treating mastitis probably requires the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…Yet, only L. rhamnosus ATCC 7469 and L. plantarum 2/37 could form their own biofilms to replace with the pathogenic ones. 63 Additionally, the L. plantarum WCFS1 and NA7 biofilms produce extracellular molecules with immunomodulatory and growth inhibitory properties against food pathogens (S. aureus, E. coli O157:H7, L. monocytogenes, and Salmonella enterica). All the studied Lactobacillus strains had an anti-inflammatory effect in the in vitro, while just L. fermentum NA4 displayed a protective effect in vivo.…”
Section: Probiotic Biofilms Against Pathogenic Biofilmmentioning
confidence: 99%
“…Yet, only L. rhamnosus ATCC 7469 and L. plantarum 2/37 could form their own biofilms to replace with the pathogenic ones. 63 Additionally, the L. plantarum WCFS1 and NA7 biofilms produce extracellular molecules with immunomodulatory and growth inhibitory properties against food pathogens (S. aureus, E. coli O157:H7, L. monocytogenes, and Salmonella enterica). All the studied Lactobacillus strains had an anti-inflammatory effect in the in vitro, while just L. fermentum NA4 displayed a protective effect in vivo.…”
Section: Probiotic Biofilms Against Pathogenic Biofilmmentioning
confidence: 99%
“…Encouraging results were obtained where Lactobacillus perolens, Lactococcus lactis and Lactobacillus casei were used against several mastitis-causing pathogens in vitro (Klostermann et al 2008;Beecher et al 2009;Frola et al 2012;Bouchard et al 2013;Assis et al 2015). These lactic acid bacteria that are part of the indigenous microbiota of the teat canal can be used at the dry-off period, because they can stimulate the immune response of the cow (Pellegrino et al 2017), they can remove S. aureus biofilms (Wallis et al 2019), and they can modulate the internalization of pathogens within host cells (Espeche et al 2012). However, it was suggested that L. casei should be used for prevention rather than treatment of S. aureus mastitis (Bouchard et al 2013).…”
Section: Alternative Therapeutic Modalities and Prophylactic Measuresmentioning
confidence: 99%
“…2017), they can remove S. aureus biofilms (Wallis et al . 2019), and they can modulate the internalization of pathogens within host cells (Espeche et al . 2012).…”
Section: Introductionmentioning
confidence: 99%
“…promising results in the prevention of mastitis. The biofilm formation inside the udder either serves as a barrier against pathogens 17 or disrupts and replaces biofilms formed by pathogens 18 . The latter could have been driven by interspecies interactions: high growth rates and dominance of probiotic organisms over other biofilm formers 19 and substrate competition 20,21 .…”
Section: Probiotic Bacteria Capable Of Biofilm Formation Have Also Shownmentioning
confidence: 99%